Lightening composition and well cementation cement slurry containing same

By adding a lightening composition of perlite powder, microsilicon and fly ash of specific proportions and particle sizes to the cementing cement slurry, the problems of increasing density and low strength of the existing low-density cement slurry under high pressure are solved, and high-strength and low-density cement slurry is achieved, thereby improving the cementing quality.

CN119841568APending Publication Date: 2025-04-18SINOPEC OILFIELD SERVICE CORPORATION +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311335063.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When the liquid column pressure of the existing low-density cement slurry is greater than 25MPa, the foam is compressed and the water seepage of the floating beads increases the density of the slurry, which is long initial setting time, large water loss, and low cement stone strength, which cannot meet the requirements of the sealing oil layer section.

Method used

Using a lightening composition including perlite powder, microsilicon and fly ash, a cementing cementing slurry with a high-strength lightening composition is prepared by adjusting its mass ratio and particle size range, combined with a base cementing cement slurry.

Benefits of technology

It effectively reduces the density of cement slurry, improves its thickening performance and compressive strength under high pressure, solves the problems of high cement slurry density, low strength and pressure bearing capacity, and improves the cementing quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004495455540000071
    Figure BDA0004495455540000071
Patent Text Reader

Abstract

The invention provides a lightening composition and a well cementation cement slurry containing the same. The lightening composition comprises crushed crude pearlite, micro-silicon and fly ash.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a lightening composition, in particular a lightening composition for reducing the density of cement slurry. Background Art

[0002] At present, complex formation reservoirs such as deep ancient buried hills and marine carbonate fractured reservoirs have become an important direction of exploration and development. Fractured reservoirs such as buried hills and carbonates have low formation pressure bearing capacity and serious leakage. Conventional density cement slurry system, although high strength, can meet the requirements of oil layer segment sealing, but the formation that is prone to leakage causes cement slurry leakage during construction, pollutes the reservoir, and even leads to construction risks. Low-density cement slurry can effectively reduce the pressure of cement slurry column, and can meet the requirements of leaky wells and return wellheads. It is the main technical measure to solve the cement slurry leakage during cementing of leaky wells or leaky wells. However, when the liquid column pressure of existing low-density cement slurry systems such as foam and floating beads is greater than 25MPa, foam slurry and floating bead low-density cement slurry will have foam compression and floating bead water seepage, which will increase the slurry density, long initial setting time, large water loss, and low cement stone strength, which cannot meet the requirements of sealing oil layer segments. Therefore, the leakage and poor cementing quality caused by high cement slurry density and low strength in the cementing process need to be solved urgently. Summary of the invention

[0003] One of the present inventions provides a lightening composition comprising perlite powder, microsilica and fly ash.

[0004] In a specific embodiment, the average particle size of the pearlite powder is 80 μm to 95 μm.

[0005] In a specific embodiment, the average particle size of the micro-silicon is 3.5 μm to 5 μm.

[0006] In a specific embodiment, the average particle size of the fly ash is 35 μm to 45 μm.

[0007] In a specific embodiment, the mass ratios of the perlite powder, the microsilica and the fly ash are (4-8):(2-4):(1-4), respectively.

[0008] In a specific embodiment, the mass ratio of the perlite powder, the microsilica and the fly ash is (3-24):(3-6):3.

[0009] The second aspect of the present invention provides a cementing slurry, which includes a basic cementing slurry and the lightening composition described in any one of the present inventions, wherein the basic cementing slurry includes cement, a dispersant, a fluid loss reducer, a retarder and water.

[0010] In a specific embodiment, based on 100 parts by mass of the cement, the amount of the lightening composition is 40 to 60 parts by mass.

[0011] In a specific embodiment, based on 100 parts by mass of the cement, the amount of the dispersant is 0.5 to 1.0 parts by mass, the amount of the fluid loss reducer is 1 to 1.5 parts by mass, and the amount of the retarder is 0.25 to 0.5 parts by mass.

[0012] In a specific embodiment, the cement, the dispersant, the fluid loss additive and the mitigation composition are used as solid phases, water and a liquid retarder are used as liquid phases, and the mass ratio of the solid phase to the liquid phase is 1:(0.8 to 1.2).

[0013] In a specific embodiment, the dispersant is at least one of SWJZ-1, USZ, and SWJZ-4.

[0014] In a specific embodiment, the fluid loss additive is at least one of SWJ-1, SWJ-2, SWJ-7, CG610S-D, and BS100.

[0015] In a specific embodiment, the retarder is at least one of SWH-1, SWH-7, and BS200-R.

[0016] Beneficial effects of the present invention:

[0017] The present invention provides a high-strength lightening composition for cementing slurry, which can solve the problems of high density, low strength and pressure bearing capacity of cementing slurry, poor cementing quality, and cementing return to the wellhead in a serious leakage well section. The composition can be widely used in oil well cementing. In terms of direct economic benefits, it can directly bring huge economic benefits, that is, effective casing, avoiding casing corrosion, and extending the life of the oil well by half a year. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0019] Preparation of lightening compositions

[0020] Example 1

[0021] The perlite powder was purchased from Zhongxin Insulation Building Materials Factory in Pingqiao District, Xinyang City.

[0022] Microsilicon was purchased from Taihe Mineral Products Processing Plant in Lingshou County, Hebei Province.

[0023] Fly ash was purchased from Guorun Zhonghe (Beijing) Technology Development Co., Ltd.

[0024] Take 40 parts by mass of pearlite powder with an average particle size of 95 μm, 10 parts by mass of microsilicon with an average particle size of 3.5 μm, and 5 parts by mass of fly ash with an average particle size of 45 μm, put them into a double-screw mixer, mix them, and repeatedly mix them for 2 hours. After they are uniform, a lightening composition 1# is obtained.

[0025] Example 2

[0026] The perlite powder was purchased from Zhongxin Insulation Building Materials Factory in Pingqiao District, Xinyang City.

[0027] Microsilicon was purchased from Taihe Mineral Products Processing Plant in Lingshou County, Hebei Province.

[0028] Fly ash was purchased from Guorun Zhonghe (Beijing) Technology Development Co., Ltd.

[0029] Take 35 parts by mass of pearlite powder with an average particle size of 90 μm, 15 parts by mass of microsilicon with an average particle size of 4.0 μm, and 10 parts by mass of fly ash with an average particle size of 40 μm, put them into a double-screw mixer, mix them, and repeatedly mix them for 2 hours. After they are uniform, a lightening composition 2# is obtained.

[0030] Example 3

[0031] The perlite powder was purchased from Zhongxin Insulation Building Materials Factory in Pingqiao District, Xinyang City.

[0032] Microsilicon was purchased from Taihe Mineral Products Processing Plant in Lingshou County, Hebei Province.

[0033] Fly ash was purchased from Guorun Zhonghe (Beijing) Technology Development Co., Ltd.

[0034] Take 25 parts by mass of perlite powder with an average particle size of 85 μm, 15 parts by mass of microsilicon with an average particle size of 4.5 μm, and 15 parts by mass of fly ash with an average particle size of 35 μm, put them into a double-screw mixer, mix them, and repeatedly mix them for 2 hours. After they are uniform, a lightening composition 3# is obtained.

[0035] Example 4

[0036] The perlite powder was purchased from Zhongxin Insulation Building Materials Factory in Pingqiao District, Xinyang City.

[0037] Microsilicon was purchased from Taihe Mineral Products Processing Plant in Lingshou County, Hebei Province.

[0038] Fly ash was purchased from Guorun Zhonghe (Beijing) Technology Development Co., Ltd.

[0039] Take 20 parts by mass of pearlite powder with an average particle size of 80 μm, 20 parts by mass of microsilicon with an average particle size of 5.0 μm, and 20 parts by mass of fly ash with an average particle size of 40 μm, put them into a double-screw mixer, mix them, and repeatedly mix them for 2 hours. After they are uniform, a lightening composition 4# is obtained.

[0040] Comparative Example 1

[0041] The average particle size of 70 μm floating beads was purchased from Xingtai Xuou Floating Bead Factory in Hebei Province.

[0042] Microsilicon with an average particle size of 5 μm was purchased from Taihe Mineral Products Processing Plant in Lingshou County, Hebei Province.

[0043] Take 30 parts by mass of floating beads with an average particle size of 70 μm and 15 parts by mass of microsilicon with an average particle size of 5 μm, put them into a double-screw mixer, mix them, and repeatedly mix them for 2 hours. After they are uniform, a lightening composition 5# is obtained.

[0044] Preparation of cement slurry for well cementing

[0045] Example 5

[0046] 100 parts by mass of G cement (Shandong Linqu Shengwei Special Cement Co., Ltd.), 0.6 parts by mass of dispersant SWJZ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 1.0 parts by mass of fluid loss reducer SWJ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 40 parts by mass of the lightening composition 1# of Example 1, 0.1 parts by mass of liquid retarder SWH-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), and 113.18 parts by mass of water, so that the solid (G cement, dispersant, fluid loss reducer and lightening composition) liquid (liquid retarder and water) ratio is 1:0.8, and the mixture is stirred evenly according to GB / T19139 standard to obtain cementing slurry 1#.

[0047] Example 6

[0048] 100 parts by mass of G cement (Shandong Linqu Shengwei Special Cement Co., Ltd.), 0.6 parts by mass of dispersant SWJZ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 1.0 parts by mass of fluid loss reducer SWJ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 45 parts by mass of the lightening composition 2# of Example 2, 0.1 parts by mass of liquid retarder SWH-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), and 131.8 parts by mass of water, so that the solid (G cement, dispersant, fluid loss reducer and lightening composition) liquid (liquid retarder and water) ratio is 1:0.9, and the mixture is stirred evenly according to GB / T19139 standard to prepare cementing slurry 2#.

[0049] Example 7

[0050] 100 parts by mass of G cement (Shandong Linqu Shengwei Special Cement Co., Ltd.), 0.6 parts by mass of dispersant SWJZ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 1.0 parts by mass of fluid loss reducer SWJ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 50 parts by mass of the lightening composition 3# of Example 3, 0.1 parts by mass of liquid retarder SWH-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), and 151.5 parts by mass of water were mixed to make the solid (G cement, dispersant, fluid loss reducer and lightening composition) liquid (liquid retarder and water) ratio 1:1, and stirred evenly according to GB / T19139 standard to prepare cementing slurry 3#.

[0051] Example 8

[0052] 100 parts by mass of G cement (Shandong Linqu Shengwei Special Cement Co., Ltd.), 0.6 parts by mass of dispersant SWJZ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 1.0 parts by mass of fluid loss reducer SWJ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 60 parts by mass of the lightening composition 4# of Example 4, 0.1 parts by mass of liquid retarder SWH-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), and 193.8 parts by mass of water, so that the solid (G cement, dispersant, fluid loss reducer and lightening composition) liquid (liquid retarder and water) ratio is 1:1.2, and the mixture is stirred evenly according to GB / T19139 standard to prepare cementing slurry 4#.

[0053] Comparative Example 2

[0054] 100 parts by mass of G cement (Shandong Linqu Shengwei Special Cement Co., Ltd.), 0.6 parts by mass of dispersant SWJZ-1, 1.0 parts by mass of fluid loss agent SWJ-1, 0.1 parts by mass of liquid retarder SWH-1, and 44.6 parts by mass of water. G cement, dispersant, and fluid loss agent are used as solid phases, and water and liquid retarder are used as liquid phases. The mass ratio of solid phase to liquid phase is 1:0.44. Stir evenly according to GB / T19139 standard to prepare basic cementing slurry, which is represented by cementing slurry D1#.

[0055] Comparative Example 3

[0056] 100 parts by mass of G cement (Shandong Linqu Shengwei Special Cement Co., Ltd.), 0.6 parts by mass of dispersant SWJZ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 1.0 parts by mass of fluid loss reducer SWJ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 35 parts by mass of the lightening composition 1# of Comparative Example 1, 0.1 parts by mass of liquid retarder SWH-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), and 122.8 parts by mass of water, so that the solid (G cement, dispersant, fluid loss reducer and lightening composition) liquid (liquid retarder and water) ratio is 1:0.9, and the mixture is stirred evenly according to GB / T19139 standard to prepare cementing slurry D2#.

[0057] Comparative Example 4

[0058] 100 parts by mass of G cement (Shandong Linqu Shengwei Special Cement Co., Ltd.), 0.6 parts by mass of dispersant SWJZ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 1.0 parts by mass of fluid loss reducer SWJ-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), 45 parts by mass of the lightening composition 1# of Comparative Example 1, 0.1 parts by mass of liquid retarder SWH-1 (Shengli Oilfield Bohai Cementing Engineering Technology Co., Ltd.), and 131.8 parts by mass of water, so that the solid (G cement, dispersant, fluid loss reducer and lightening composition) liquid (liquid retarder and water) ratio is 1:0.9, and stirring is carried out according to GB / T19139 standard, but due to poor compatibility, it cannot be prepared into cementing cement slurry.

[0059] Application Example 1

[0060] The cement slurries of Examples 5 to 8 and Comparative Examples 1 and 2 were tested for cement slurry density according to GB / T19139 standard.

[0061] The cement slurry density test results are shown in Table 1.

[0062] Table 1 Cement slurry density test results

[0063] Example <![CDATA[Cement slurry density / g / cm 3 > Example 5 1.30 Example 6 1.25 Example 7 1.15 Example 8 1.08 Comparative Example 2 1.98 Comparative Example 3 1.40

[0064] It can be seen from Table 1 that the density of cement slurry can be reduced from 1.98 g / cm 3 The amount of lightening compound added is reduced to 1.1 g / cm 3 The density of the cementing slurry prepared using the lightening composition of the present invention is generally better than that of Comparative Example 3.

[0065] Application Example 2

[0066] The cement slurry thickening performance test was performed on the cement slurries of Examples 5 to 8 and Comparative Examples 2 and 3 according to GB / T19139 standard. The thickening performance test was performed at a temperature of 90° C. and a pressure of 40 MPa.

[0067] The test results of cement slurry thickening performance are shown in Table 2.

[0068] It can be seen from Table 2 that the transition time of cement slurry from 30Bc to 100Bc in Comparative Example 2 without adding the lightening composition is 40min; the transition time of cement slurry from 30Bc to 100Bc in Comparative Example 3 with adding the conventional lightening composition 5# is 35min; and the transition time of cement slurry from 30Bc to 100Bc with adding lightening compositions 1# to 4# is below 25min. It can be seen that the thickening transition time of cementing slurry with the lightening composition of the present invention can be greatly shortened, which can effectively solve the weight loss problem in the solidification process of cement stone, thereby improving the anti-gas channeling ability of cementing slurry.

[0069] Table 2 Cement slurry thickening test results

[0070]

[0071] Application Example 3

[0072] According to GB / T19139 standard, the compressive strength of cement paste prepared by curing the cement slurries of Examples 5 to 8 and Comparative Examples 2 and 3 at 90° C. and normal pressure for 48 hours was tested. The test results are shown in Table 3.

[0073] Table 3 Cement stone compressive strength test results

[0074] Example Cement stone compressive strength / MPa Example 5 12 Example 6 10 Example 7 9.5 Example 8 8.5 Comparative Example 2 29 Comparative Example 3 6.0

[0075] According to the results in Table 3, the compressive strength of the low-density cement paste of Comparative Example 3 is only 6.0 MPa, while the compressive strength of the low-density cement pastes of Examples 5 to 8 are all above 8 MPa.

[0076] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A lightening composition comprising perlite powder, microsilica and fly ash.

2. The lightening composition according to claim 1, characterized in that The average particle size of the pearlite powder is 80 μm to 95 μm.

3. The lightening composition according to claim 1, characterized in that The average particle size of the micro silicon is 3.5 μm to 5 μm.

4. The lightening composition according to claim 1, characterized in that The average particle size of the fly ash is 35 μm to 45 μm.

5. The lightening composition according to claim 1, characterized in that The mass ratio of the pearlite powder, the microsilica and the fly ash is (4-8): (2-4): (1-4) Preferably, the mass ratio of the perlite powder, the microsilica and the fly ash is (3-24):(3-6):

3.

6. A cementing slurry comprising a base cementing slurry and a lightening composition according to any one of claims 1 to 5; Preferably, the basic cementing slurry comprises cement, dispersant, fluid loss reducer, retarder and water.

7. The cementing slurry according to claim 6, characterized in that: Based on the mass of the cement as 100 parts by mass, the amount of the lightening composition is 40 to 60 parts by mass; Preferably, based on 100 parts by mass of the cement, the amount of the dispersant is 0.5 to 1 part by mass, the amount of the fluid loss reducer is 1 to 1.5 parts by mass, and the amount of the retarder is 0.25 to 0.5 parts by mass; Preferably, the cement, the dispersant, the fluid loss agent and the lightening composition are used as solid phases, water and a liquid retarder are used as liquid phases, and the mass ratio of the solid phase to the liquid phase is 1:(0.8 to 1.2).

8. The cementing slurry according to claim 6, characterized in that: The dispersant is at least one of SWJZ-1, USZ, and SWJZ-4.

9. The cementing slurry according to claim 6, characterized in that: The fluid loss reducer is at least one of SWJ-1, SWJ-2, SWJ-7, CG610S-D, and BS100.

10. The cementing slurry according to claim 6, characterized in that: The retarder is at least one of SWH-1, SWH-7, and BS200-R.

Citation Information

Cited By

  • Low-density cement paste as well as preparation method and application thereof

    CN121135264A

  • Low density cement slurries, methods of making and using same

    CN121135264B